A genomic test of sex-biased dispersal in white sharks - Romuald Laso-Jadart; Shannon L. Corrigan; Lei Yang; Szu-Hsuan Lee; Elise J. Gay; Olivier Fedrigo; Christopher G. Lowe; Gregory Skomal; Geremy Cliff; Mauricio Hoyos Padilla; Charlie Huveneers; Kady Lyons; et al. (Proceedings of the National Academy of Sciences, 2025)
Mitonuclear discordance has been observed in several shark species. Female philopatry has often been invoked to explain such discordance but has never been explicitly tested. Here, we focus on the white shark, for which female philopatry has been previously proposed, and produced a chromosome-level genome, high-coverage whole-genome autosomal, and uniparental datasets to investigate mitonuclear discordance. We first reconstructed the historical population demography of the species based on autosomal data. We show that this species once comprised a single panmictic population, which experienced a steady decline until recent times when it fragmented into at least three main autosomal genetic groups. Mitochondrial data depict a strikingly different picture, inconsistent with the spatial distribution of autosomal diversity. Using the demographic scenario established from autosomal data, we performed coalescent and forward simulations to test for the occurrence of female philopatry. Coalescent simulations showed that the model can reproduce the autosomal variability, confirming its robustness. A forward simulation framework was further built to explicitly account for a sex-biased reproduction model and track both autosomal and uniparental markers (Y chromosome and mitochondrial DNA). While our model generates data that are consistent with the observed Y chromosome variation, the mitochondrial pattern is never reproduced even under extreme female philopatry (no female migration), strongly suggesting that demography alone cannot explain the mitonuclear discordance. Our framework could, and perhaps should, be extended to other shark species where philopatry has been suggested. It is possible that the proposed widespread occurrence of female philopatry in sharks should be revisited.